The Ritual Character of the Brand: the Challenge of the New Spaces between Consumerism and Religion - Bernard Sawicki (Polonia Sacra, 2017)
In a world where everything is connected even realms which seem remote can be close. The ways of commerce and religion have always crossed, but recently one can speak, at least, about mutual inspiration. To deal with this complex, but fascinating and highly relevant phenomenon it is good to find some categories which make a comparison possible. One of them is rite, whose importance in modern branding is growing. The fact that a sense of community and relations construct both good brands and profound religious experience seems to open up new horizons in a dialogue between economics and religion.